Baseline sociodemographic characteristics of participants and dropout in Web-based weight reduction program in Serbia - Dragana Brdaric (Frontiers Media S.A., 2015)
BACKGROUND: Standard treatments of obesity are becoming very large economic burden to the health systems even in the most developed countries (Finkelstein, Trogdon, Cohen & Dietz, 2009) and are available only to a limited number of people (Manzoni et al., 2011; Womble et al., 2004). Having that in mind, the use of digital technology and the Internet has the potential to provide cost-effective and accessible weight reduction treatment. However, overview of research highlights several issues that need to be overcome in order to have efficient web based weight loss intervention. One of these challenges is the very high drop-out rate of respondents. Percentage of respondents who discontinue participation in the study before the expiry of the duration of treatment can range from 6 to 80%, even when payment or reward of subject participation is introdused (Cook et al., 2007; Levine, Savarimuthu, Squires, Nicholson & Jay, 2015). OBJECTIVE: Construction and validation of web based programs in economically less developed countries is still in its infancy. The program that was created by our research team is the first web based weight-loss program in Serbia. Due to this, this research aims to investigate whether and to what extent such a web based weight loss program can attract attention and commitment to customers, as well as to describe the basic sociodemographic characteristics of the users of such program in Serbia. METHODS: Web based weight loss program called Health on menu was created using Transtheoretical model as background for developing the interventions. The program consists of 60 interventions with the following contents: Education about the causes and consequences of certain eating behaviors, information on strategies that help reducing the body weight, techniques for decision making and goal setting; techniques for practicing skills that enhance self-efficacy, techniques for raising and maintaining motivation, as well as dealing with challenges and stimulus control, reinforcement management, seeking support, etc. The program allows interactive use of the described contents. Respondents are able to analyze and solve those tasks through the possibility of entering self monitoring of food and drink intake, monitoring of physical activity and other parameters of progress, formulation of goals, entering advantages and disadvantages of the behaviour change related decisions, etc. Participants were collected from the beginning of May, 2015, until the end of July, 2015. via internet, social networks and local written and online media in the Autonomous Province of Vojvodina, Serbia. Data were collected online and they included pretreatment survey, and two additional surveys after 15 and 90 days of using web based program . Respondents were invited to fill out the questionnaires via notifications within the program. In addition, respondents were given a reminder to complete the questionnaire via email. Participants did not receive any financial or other compensation for participation in the study. In order to encourage the use of the program, participants were receiving email reminders if they were not active for more than a week. RESULTS: 368 participants were registered as interested in taking part in the program. 87% were female with the mean (SD) age of 33.24 (10.69). Mean (SD) BMI of those registrated users were 26,17 (4.88). 70% were classified as not having any serious health problem. 65.8 % of them have higher education, 25.8% have further education, while only 8.4% have elementary education. Of those 368 registered users, only 182 actually enrolled in the program Health on menu. Those 182 participants were 80.2% female with the mean (SD) age of 34 (12.08). Mean (SD) BMI were 26,61 (4.99). Of all participants, 58.2% were classified as not having any serious health problem. 63.7 % participants have higher education, 21.4% have further education, while 8.8% have elementary education. Health on menu participant's retention rate after 15 and 90 days were 25.5% and 7.14% respectively. CONCLUSIONS: The findings show that the majority of participants of web-based weight loss program Health on menu were adult women who are highly educated. The average BMI of the respondents fall into the category of overweight. The findings demonstrate very high prevalence of attrition among participants. Given that this is the first time that this kind of web based program is introduced to Serbian participants, these results emphasize the importance of further continuation of such research. Also, those preliminary results highlight the need for evidence-based strategies in order to improve use of web based weight loss programs.